Can Biomass Mastication Assist the Downstreaming of Polyhydroxyalkanoates Produced from Mixed Microbial Cultures? - Souza, Hiléia K. S. (2023)
Funding Information: Additional funding from the Portuguese Foundation for Science and Technology (FCT) in the framework of the contract CEECINST/00156/2018 is also acknowledged. Publisher Copyright: © 2023 by the authors.